2017
DOI: 10.1097/md.0000000000005647
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of HCV induced—Esophageal varices in Egypt

Abstract: Esophageal varices is one of the most important comorbidity related liver cirrhosis, patients usually presented with hematemesis, melena, or both, ultimately 20% is the mortality during the first attack, hence we aimed to investigate the incidence of such esophageal varices related chronic Hepatitis C virus (HCV) in randomized Egyptian population.One thousand eighteen Egyptian patients, aged between 17 and 58 years, positive for Hepatitis C virus genotype 4 (HCV-4) by enzyme linked immunosorbent assay Ab and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…In our study, there was no statistically significant difference between the two studied groups in baseline demographic and clinical characteristics which matches with previous studies comparing EUS-guided techniques versus conventional endoscopic technique 8 23 . The most common cause of portal hypertension in our study was chronic HCV-induced cirrhosis, this matches with data about prevalence of chronic HCV in Egyptian population; being the most common cause of portal hypertension 24 . As regards liver function assessment, our results found that most cases have CTP class A (83.7 %) and median MELD score nine which matches with the results published by Robles-Medranda et al which stated that median MELD score among 60 cases with GVs was 9.5 and CTP class A was the most common class 25 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, there was no statistically significant difference between the two studied groups in baseline demographic and clinical characteristics which matches with previous studies comparing EUS-guided techniques versus conventional endoscopic technique 8 23 . The most common cause of portal hypertension in our study was chronic HCV-induced cirrhosis, this matches with data about prevalence of chronic HCV in Egyptian population; being the most common cause of portal hypertension 24 . As regards liver function assessment, our results found that most cases have CTP class A (83.7 %) and median MELD score nine which matches with the results published by Robles-Medranda et al which stated that median MELD score among 60 cases with GVs was 9.5 and CTP class A was the most common class 25 .…”
Section: Discussionsupporting
confidence: 92%
“…In the previous study, upper GIT endoscopy findings were more frequent and less serious than colonoscopy findings and meanwhile colon cancer was the most common lesion in colonoscopy agreed with Abdel-Aty et al [23].…”
Section: Results Of Previous Studies Have Implicatedsupporting
confidence: 80%
“…Several studies conducted globally on this topic have produced a wide range of results. The non-adherence rate in a global study conducted was 45% and a significant number of the hypertensive patients with co-morbidities were non-adherent to treatment [ 14 ]. The non-adherence rate from community-based studies in Bangladesh and Vietnam were as high as 85 and 49.8% respectively [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%